Switch & Knit Stitch Dictionary : Choose any yarn and any of the 12 PATTERNS for cowls, hats, sweaters & more * Customize with over 85 STITCH PATTERNS * 700+ DESIGN POSSIBILITIES /: Choose any yarn and any of the 12 PATTERNS for cowls, hats, sweaters & more * Customize with over 85 STITCH PATTERNS * 700+ DESIGN POSSIBILITIES. (2020) - Hedrick, Tabetha
No abstract available